Self-Esteem of Patients Receiving Chemotherapy Treatment in a Tertiary Care Hospital Karachi, Pakistan - Daizi Jafar; Fozia Pesnani; Shireen Arif; Alia Nasir (ziauddin University, 2020)
Background: Cancer is becoming serious and emerging health concern around world. In Pakistan, 8% of all deaths are due to cancer as one of the major cause. Treatment of cancer consists of surgical management, radiation, chemotherapy, hormone therapy, immunotherapy, and combined therapy. Psychological imbalance is observed during treatment and cause altered self-esteem, which requires psychological modification. The study aimed to assess the alteration in self-esteem after receiving chemotherapy. Methods: This research study was cross-sectional study, in which fifty individuals were selected between ages of 18-80 years from oncology unit of tertiary care hospital. A self-administered questionnaire consist of Rosenberg self-esteem scale assessing the self-esteem was administered. Teaching sessions for developmental change towards giving education on increasing self-esteem of patients were conducted for oncology nurses. Results were analyzed using SPSS version 22. Results: Since, 44% male and 56% female were participated. In all surveyed individuals 96% participants identified with average normal self-esteem, 3% participants had low self-esteem, whereas, only 1% participants had high self-esteem. Conclusion: This research study revealed that most of the patient suffering cancer had average self-esteem. Therefore, there is need to work on strategies to promote psychological well-being of patients, aiming to uphold and rehabilitate emotional aspects of cancer patients.